Oral traditions and the verbal arts: A guide to research practices - Finnegan, Ruth (London Routledge, 1992)
Provides up-to-date guidance on how to approach the study of oral forms and their performances, examining both the practicalities of fieldwork and the methods by which oral texts and performances can be observed, collected and analysed.